Buletin Peternakan : ANALISIS KELAYAKAN FINANSIAL USAHA PENGGEMUKAN SAPI SIMMENTAL PERANAKAN ONGOLE DAN FAKTOR YG BERPENGARUH TERHADAP JUMLAH KEPEMILIKAN PADA PETERNAKAN RAKYAT DI KAB KARANGANYAR - Josua Sahala (Peternakan UGM, 2016)
This study was done to determine the financial feasibility of beef cattle fattening and the factors affecting on amount of cattle ownership of small scale farmer in Karanganyar District. The location quotient (LQ) selected were Jenawi, Jatiyoso and Mojogedang sub-districts. Sampling respondents were determined by purposive sampling of 40 SimPO cattle farmers.